2022
DOI: 10.7150/ijbs.70289
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma-derived exosomes deliver lncARSR to induce macrophage polarization and promote tumor progression via STAT3 pathway

Abstract: Tumor-derived exosomes play a pivotal role in regulating tumor progression by mediating crosstalk between tumor cells and immune cells such as macrophages within the tumor microenvironment. Macrophages can adopt two distinct polarization statuses and switch between M1 or M2 activation phenotypes in response to the different external stimuli. However, the role of tumor derived exosomes in the macrophage phenotypic switch and tumor development have not been elucidated in renal cell carcinoma (RCC). Here we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Exosomes derived from renal cell carcinoma cells were reported to promote macrophage polarization, cytokine release, phagocytosis, angiogenesis, and tumor development. Overexpression of long noncoding RNA ARSR induced phenotypic and functional changes of macrophages in vitro and promoted tumor growth in vivo , while knockout of long noncoding RNA ARSR impaired the exosome-mediated polarization of macrophages [ 37 ]. Luo et al established an in vitro cell model and an in vivo mouse model of Mycobacterium tuberculosis infection and conducted negative pressure treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from renal cell carcinoma cells were reported to promote macrophage polarization, cytokine release, phagocytosis, angiogenesis, and tumor development. Overexpression of long noncoding RNA ARSR induced phenotypic and functional changes of macrophages in vitro and promoted tumor growth in vivo , while knockout of long noncoding RNA ARSR impaired the exosome-mediated polarization of macrophages [ 37 ]. Luo et al established an in vitro cell model and an in vivo mouse model of Mycobacterium tuberculosis infection and conducted negative pressure treatment.…”
Section: Discussionmentioning
confidence: 99%
“…found that the knockdown of lncRNA PCAT6 could prevent its positive effect on M2 polarization and in turn accelerated NSCLC development ( 75 ). lncARSR-containing EVs derived from renal cell carcinoma achieve a similar effect via the STAT3 pathway ( 76 ). MiR-147a/ARID3A axis is activated under hypoxia condition by hepatocellular carcinoma (HCC)-derived EVs delivering lncRNA HMMR-AS1 ( 77 ).…”
Section: Macrophagementioning
confidence: 99%
“…They demonstrated that exosomal miR-549a could reduce the expression level of hypoxia-inducible factor 1 alpha subunit (HIF1α) by binding to the 3’-UTR region of HIF1α mRNA, which in turn attenuate tumor angiogenesis and endothelial cell migration in ccRCC ( 31 ). A new study found that ccRCC-derived exosomes can activate the miR34/miR449-STAT3 signaling pathway by delivering lncARSR, which in turn promotes the transformation of M1 macrophages to M2 and enhances the phagocytic ability of macrophages, which in turn induces angiogenesis and ultimately promotes the development and progression of tumors ( 32 ). In summary, ccRCC cell-derived exosomes participate in tumor angiogenesis by delivering a variety of miRNA and protein molecules, thereby affecting the metastasis process of ccRCC.…”
Section: Tumor-derived Exosomes Promote Metastasis Of Ccrccmentioning
confidence: 99%